Bandwidth Efficient Broadcast Protocols in MANETs: A Review - Samal, CK; Choudhury, RK (International Journal of Computer Sciences and Engineering, 2025)
Mobile ad hoc networks has been facing problems, when nodes are transmission in multi-hop nodes that time a contention and congestion due to node mobility, the network has unpredictable characteristics; its topology changes and signals strength fluctuates because of the broadcast nature of radio transmission. The broadcast operation is very important in MANETs and major challenges to reducing redundant, rebroadcast and broadcast latency problems. In this paper we comparative study of the DFCN and PEGSP algorithms for efficiently bandwidth utilize in multi-hop MANETs. Our validated simulation result shows that PEGSP algorithm is high reliability and high efficiency, channel's bandwidth is efficiently utilized in wide area networks context of low speed of mobile nodes. The DFCN protocol operates well in high density and low density networks, it well in high speed mobile nodes. Nodes are high reachability within transmission range of the network, this protocol is advantages for energy conservation in multi-hop mobile ad hoc network.